Revitalization of Pasambahan Manjapuik Marapulai as Part of Maintaining Efforts of Minangkabau Culture - SRIMAHARANI TANJUNG (Journal of Oral Traditions, 2019)
The current of increasingly strong modernization has caused the local wisdom of a culture to be eliminated and replaced with a new form of habit instantly. This condition causes humans escape beyond the scope of their original tradition, and cause them become a crisis of identity and cultural breakdown. This paper aims to show the importance of revitalizing the tradition of Pasambahan manjapuik marapulai as part of efforts to preserve the Minangkabau culture. This type of research is descriptive qualitative. Sources of data obtained from field observations and interviews with informants and study documentation. The results showed that in order to revitalize the tradition of Pasambahan manjapuik marapulai, this can be done through three (3) stages, namely: activating, managing and inheritance. Activating can be done by socializing Minangkabau culture through education, re-functioning the traditional process, and forming a youth organization. Managing can be done by managing training time, promoting and involving youth in a series of events. Inheritance can be done through radio broadcasting, airing custom shows on local television, posting cultural advertisement and inventory.